Landasan pengembangan teori belajar dan psikologi perkembangan menurut al-qur’an dan hadist - Aulia, Habibah Shofi Futuhil (Maliki Interdisciplinary Journal, 2025)
Education in the modern era faces increasingly complex challenges due to advancements in technology and information. Therefore, a balanced approach between intellectual, emotional, and spiritual intelligence is necessary. The Qur’an and Hadith provide a comprehensive theoretical foundation for the development of psychology and learning theories relevant to contemporary contexts. This article analyzes the integration of individual developmental psychology concepts in the digital age and formulates effective value-based educational strategies. By emphasizing the importance of holistic education, the article explains how Islamic principles can be applied in modern educational practices. Through a deep understanding of human developmental characteristics, education is expected to shape individuals who are not only academically intelligent but also possess noble character and high integrity. The use of value-based moral and spiritual learning methods is crucial for equipping the younger generation to face the challenges of the times. Thus, the integration of psychological concepts and education based on the Qur’an and Hadith is expected to create individuals who are ready to contribute positively to society.